Defending Democracy: Inoculation's Efficacy in Protecting First Amendment Attitudes. Issue 1 (1st January 2020) - Parker, Kimberly A.; Geegan, Sarah; Ivanov, Bobi; Slone, Amanda; Silberman, Will; Martin, Joe; Hester, Erin; Goatley-Soan, Sean; Anderson, August; Herrington, Taban; Riker, Seth
ABSTRACT: Although it may be tempting to assume that people's attitudes toward the First Amendment are resolute, extant research and the findings of this investigation suggest the opposite: that Americans' First Amendment attitudes are quite susceptible to persuasion. This investigation applied inoculation theory as an avenue through which attitudes toward the First Amendment could be strengthened and protected against counter-attitudinal persuasive attacks. The results of this three-phase experiment show that inoculation-based strategies are capable of both strengthening and protecting First Amendment attitudes against pressures to support narrowing the scope of the First Amendment. In addition, inoculation proved to be a successful strategy in protecting the certainty (or conviction) with which First Amendment attitudes are held.